Chan–Lam cross-coupling reactions promoted by anionic copper(I)/iodide species with cationic methyl-((pyridinyl)-pyrazolyl)pyridin-1-ium. Issue 44 (3rd November 2016) - Xue, Jiang-Yan; Li, Jun-Chi; Li, Hong-Xi; Li, Hai-Yan; Lang, Jian-Ping
Abstract: Four anionic ligands including 1-methyl-3(or 4)-(1-(pyridin-2-yl)-1 H -pyrazol-3-yl)pyridin-1-ium iodide ([3, 2′-pypzpym]I, [4, 2′-pypzpym]I) and 1-methyl-3(or 4)-(3-(pyridin-2-yl)-1 H -pyrazol-1-yl)pyridin-1-ium iodide ([2, 3′-pypzpym]I, [2, 4′-pypzpym]I) are prepared. Reaction of CuI with [3, 2′-pypzpym]I affords a mononuclear complex [CuI2 (3, 2′-pypzpym)] (1 ) and a one-dimensional coordination polymer [(Cu4 I6 )(3, 2′-pypzpym)2 ] n (2 ). Analogous reactions of CuI with [4, 2′-pypzpym]I, [2, 3′-pypzpym]I or [2, 4′-pypzpym]I yield [Cu4 I6 (4, 2′-pypzpym)2 ] (3 ), [CuI2 (2, 3′-pypzpym)] (4 ) and [CuI2 (2, 4′-pypzpym)] (5 ), respectively. Relative to that of CuI, complexes1 –5 exhibit enhanced catalytic activities towards the Chan–Lam cross-coupling reactions of imidazole and arylboronic acids in a H2 OMeCN (v/v=2:1). This catalytic system is involved in the CN cross-coupling reaction and works for a variety of imidazole derivatives as well as arylboronic acids with different electronic properties. Graphical abstract: